Corrosion resistance tables : metals, nonmetals, coatings, mortars, plastics, elastomers and linings, and fabrics - Schweitzer, Philip A. (Corrosion technology (New York, N.Y.), 1995)
This edition presents corrosion resistance data on all important materials currently used to fabricate systems, commodities and structures that come into contact with chemicals.